Analisis Kajian Linguistik Modern dalam Pembelajaran Bahasa Arab - Hapianingsih, Eliana; Fadli, Adi (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2024)
This research aims to study and analyze modern linguistic studies in Arabic language learning. This research is a type of library research, the data in this research are journals, articles, websites and books that discuss modern linguistics from the aspects of meaning, objects, objectives, scope and benefits of studying modern linguistics. This research is a library research study, so the data analysis technique used in this research is content analysis technique and the data is presented in a qualitative descriptive manner. The results of this research are that linguistics is a science that studies and examines language, sounds, human signals related to language phenomena, then the scope of study of modern linguistics is first, phonology, where language is a spoken form, not written. Second, morphology is a science that studies the methods of word formation and the verbal changes that occur in these words. The third is semantics, namely the science that studies meaning and examines the branch of linguistics that is related to the theory of meaning. Fourth is syntax, which is the study of how to form sentences from different words. Then the benefits of linguistic theory in developing Arabic language teaching such as sociolinguistics, contrastive and psycholinguistics. The role of linguistics in developing Arabic language teaching is an important tool for determining language teaching targets and explanations, because linguistics is a tool used by language teachers to describe and analyze language which of course will help the language teaching process. A good learning process always starts with a thorough plan. Careful planning will show optimal results in learning. Planning is the process of preparing something that is carried out to achieve predetermined goals.